The Gut Hormones in Appetite Regulation - Keisuke Suzuki; Channa N. Jayasena; Stephen R. Bloom (Journal of Obesity)
Obesity has received much attention worldwide in association with an increased risk of cardiovascular diseases, diabetes, and cancer. At present, bariatric surgery is the only effective treatment for obesity in which long-term weight loss is achieved in patients. By contrast, pharmacological interventions for obesity are usually followed by weight regain. Although the exact mechanisms of long-term weight loss following bariatric surgery are yet to be fully elucidated, several gut hormones have been implicated. Gut hormones play a critical role in relaying signals of nutritional and energy status from the gut to the central nervous system, in order to regulate food intake. Cholecystokinin, peptide YY, pancreatic polypeptide, glucagon-like peptide-1, and oxyntomodulin act through distinct yet synergistic mechanisms to suppress appetite, whereas ghrelin stimulates food intake. Here, we discuss the role of gut hormones in the regulation of food intake and body weight.